Intervensi Senam Kecerdasan RTD Untuk Membantu Menurunkan Tingkat Depresi, Kecemasan Dan Stress Pada Klien Dewasa - Imadatus Sa'adati, Tatik; Luthfi Athmasari (Faculty of Ushuluddin and Humanities, 2025)
Mental health can be measured through levels of depression, anxiety, and stress. One motoric and spiritual-based intervention that can help reduce stress levels is RTD Intelligence Gymnastics, developed by Aas Rukasa with an approach centered on faith in Allah SWT. This study aims to analyze the effectiveness of RTD Intelligence Gymnastics in reducing depression, anxiety, and stress levels in adult clients. The research method used is an experimental study with a One-Group Pretest-Posttest design. In this study, the independent variable is RTD Gymnastics as a therapeutic process, while the dependent variable is the level of depression, anxiety, and stress. The subjects of this study were three adult female clients experiencing psychological problems (depression, stress, and anxiety) who joined the RTD Gymnastics community. Measurements were conducted using the Depression, Anxiety, and Stress Scale (DASS). The results showed that for Client A, the average DASS score before participating in RTD Gymnastics was 10.67, which decreased to 6.67 after the intervention (a reduction of 4 points). For Client B, the average DASS score before the intervention was 14, which decreased to 2 after participating in RTD Gymnastics (a reduction of 12 points). For Client C, the average DASS score before RTD Gymnastics was 20.67, which decreased to 0.67 after the intervention (a reduction of 20 points). These results indicate a decrease in DASS scores for all participants after engaging in the gymnastics program. RTD Intelligence Gymnastics has been proven to be beneficial in reducing individual levels of depression, anxiety, and stress. Keywords: RTD Intelligence Gymnastics, Levels of Depression, Anxiety, and Stress